(untitled) (Palíndromo, 2021)
This essay addresses three artistic propositions made by Guilherme Vaz between 1969 and 1970 for the Salão da Bussóla at the Museum of Modern Art in Rio de Janeiro, the sequential exhibition Agnes Dei at the Petite Galerie in Rio de Janeiro, and the collective exhibition Information at the Museum of Art New York City. Held in the period corresponding to his first experience in the city of Rio de Janeiro, marked by encounters and contagions with Artur Barrio, Thereza Simões, Nelson Pereira dos Santos and Frederico Morais, these propositions occur through words that are communicated in three different states: by an artistic body, written on small notes posted in the gallery, or reproduced by a loudspeaker. Our methodology consists of introducing this period from a brief artistic-biographical arc, followed by the description of his works from their context of realization and the critical dialogue with texts and artistic works, and concluded by essayistic reflections on the specificities and effects of the different voco-verbal states of words in these three propositions.